From Concept to Creation - Maricica STOICA; Carmelia Mariana BĂLĂNICĂ-DRAGOMIR; Cezar Ionuț BICHESCU; Alina Mihaela CEOROMILA; Angela Stela IVAN; Larisa ȘAVGA; Dimitrie STOICA (ACROSS)
Designing and innovation products are essential processes for maintaining the competitiveness and long-term sustainability of food manufacturing businesses. This study explores internal and external sources of ideas that drive new foods development, highlighting the importance of aligning product strategies with consumer needs and market demands. Feedback from sales representatives, consumer engagement, and experimental research serve as key internal sources, providing valuable insights to enhance product features. External sources, including market analysis, competitor monitoring, and participation in trade exhibitions, contribute to the identification of trends and opportunities for innovation. The role of specialized resources such as libraries, databases, and technical literature in supporting strategic planning and research is also emphasized. By integrating these diverse sources with creative thinking and systematic research, companies can generate market-driven product concepts and maintain a competitive edge. The results highlight the importance of a balanced strategy for idea generation to promote effective and sustainable innovations in food product development.